Information Transparency and Investment in Follow‐on Innovation* - Chen, Jeff Zeyun; Kim, Yongtae; Yang, Leo L.; Zhang, Joseph H. (Contemporary Accounting Research, 2023)
ABSTRACT This study examines the role of information transparency in facilitating peer firms' investment in follow‐on innovation. We capture information transparency with both textual and numerical information disclosed in 10‐Ks. Using patent citations to proxy for investment in follow‐on innovation, we predict and find a positive association between transparency at the knowledge source and follow‐on innovation. We further show that the effect of information transparency varies with the degree of uncertainty around technological innovation. Thus, the evidence suggests that information transparency facilitates investment in follow‐on innovation by resolving uncertainty associated with investment in technological innovation. An analysis using the cited firms' going‐private decision as a negative shock to information transparency confirms the significant effect of a cited firm's disclosure on its decision to invest in follow‐on innovation. Our study contributes to the literature on the positive externalities of peer‐firm disclosures and highlights the important role of information transparency in shaping innovation investment decisions.